Natural progression of radiographic indices in juvenile hallux valgus deformity - Sung, Ki Hyuk; Kwon, Soon Sun; Park, Moon Seok; Lee, Kyoung Min; Ahn, Jonghyun; Lee, Seung Yeol (Foot and Ankle Surgery, 2019)
Background: This study aimed to estimate the annual change in radiographic indices for juvenile hallux valgus (JHV) and to analyze the factors that influence deformity progression. Methods: Patients aged <15 years who had JHV and were followed up for at least 1 year were included. Hallux valgus angle (HVA), hallux interphalangeal angle, intermetatarsal angle, metatarsus adductus angle, distal metatarsal articular angle, anteroposterior talo-first metatarsal angle, and lateral talo-first metatarsal angle were evaluated. The progression rate of HVA was adjusted by multiple factors by using a linear mixed model. Results: A total of 133 feet were included. The HVA and distal metatarsal articular angle both increased by 0.8° per year (p < 0.001 and p = 0.003, respectively). HVA increased by 1.5° per year (p < 0.001) at under the age of 10, and the HVA progression in the older patients was not statistically significant. Conclusions: JHV deformity could progress with aging. Most deformity progression could occur before the age of 10 years.
Keywords: Adolescent; Aging; Child; Disease Progression; Female; Follow-Up Studies; Hallux Valgus; Humans; Male; Metatarsal Bones; Metatarsophalangeal Joint; Radiography; Retrospective Studies; Hallux valgus angle; Juvenile hallux valgus; Linear mixed model; Radiographic index